Dinoflagellate cysts in recent sediments from two semi-enclosed areas of the Western Mediterranean Sea subject to high human impact - Teodora Satta, Cecilia; Anglès, Silvia; Garcés, Esther; Lugliè, Antonella; Mario Padedda, Bachisio; Sechi, Nicola (Deep-sea research. Part II, Topical studies in oceanography, 2010)
Studies were conducted on dinoflagellate cyst assemblages from two semi-enclosed areas of the Western Mediterranean Sea subject to high human impact, Arenys de Mar harbor and the Gulf of Olbia. Sediment cores were taken from seven stations (December 2006 and August 2007) in Arenys and from eight (October 2006) and ten (May 2007) stations in Olbia. Of the 42 morphotypes found in the sediments collected at the two sites, 27 were identified at the species level, representing 10 genera. The most common cysts were those of Scrippsiella trochoidea, Scrippsiella sp. 2, Gymnodiniales type 1, and Scrippsiella precaria. A number of the morphotypes had not been previously described in the literature. Total cyst abundances varied substantially between the two surveys, with an increased total density in Arenys and a decrease in Olbia. However, at the latter site, a higher abundance of cysts was recorded at more confined sampling stations. Calcareous Peridiniales, belonging to the genus Scrippsiella, dominated the cyst assemblages of both sites, while at some stations higher numbers of Gymnodiniales (Olbia) and Gonyaulacales (Arenys) were determined. Cysts of the toxic species Alexandrium minutum and A. catenella/tamarense were also detected. A. minutum was present at both sites whereas A. catenella/tamarense was found only in Olbia. Peridinium quinquecorne was recovered in the sediments of both sites. In Olbia, cysts of this species were present at high densities and were detected even in deep sediments. Species such as Pentapharsodinium cf. tyrrhenicum, Scrippsiella crystallina, S. lachrymosa, S. precaria, S. trochoidea, Protoperidinium avellanum, P. claudicans, P. compressum, P. conicum, P. cf. minutum, P. oblongum, P. pentagonum, P. subinerme, and Zygabikodinium lenticulatum were not detected as motile stages in the study areas. The results of this study, the first on dinoflagellate cyst assemblages at these two sites, further our knowledge of cyst diversity and confirm the importance of embayments and hydrographically confined areas as reservoirs for planktonic dinoflagellates.